Subtropical warming enhances North Pacific midlatitude winter storm track activity in recent decades - Pei-Chun Hsu; Huang-Hsiung Hsu; Hao-Jhe Hong; Ying-Ting Chen (npj Climate and Atmospheric Science)
Abstract Changes in storm track intensity and position are key indicators of atmospheric responses to global warming. In this study, we identified a robust northward shift and intensification of midlatitude storm track activity during boreal winters in the North Pacific since the early 1980s. This trend is linked to subtropical tropospheric warming, which has enhanced the midlatitude meridional temperature gradient. This gradient–storm track relationship is evident in both long-term trends and interannual variations. By contrast, Arctic warming weakens near-surface temperature gradients and negatively correlates with storm track activity. Additionally, tropical upper-tropospheric warming appears to strengthen the meridional gradient but induces equatorward shifts in the jet stream and storm track, countering the observed poleward trends. Numerical simulations suggest that the sea surface warming observed in the subtropical North Pacific and Indian Ocean contributes to storm track and circulation changes, providing insights into midlatitude atmospheric dynamics in the context of global warming.